Hubungan Gaya Hidup Sedentary Terhadap Kejadian Tinggi Prediabetes di Wilayah Kerja Puskesmas Johar Baru - Ambarita, Dita Dwi Lestari; Prabawati, Dewi; Hidayah, Ainun J (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2022)
Introduction: The incidence of prediabetes risk increases every year. This can occur as a result of lack on physical activity which is exacerbated by a pandemic condition that strengths people to stay at home more. Objectives: This study was conducted to determine the relationship between a sedentary lifestyle towards the incidence of prediabetes in the working area of the Johar Baru Health Center. Methods: The study design used is descriptive correlation with a cross sectional approach. The sample in this study was the community in the working area of the Johar Baru Health Center and there were 64 respondents chosen using purposive sampling technique. The Finnish Diabetes Risk Score (FINDRISC) instrument was utilized to assess the prediabetes score, while The Sedentary Behavior questionnaire used to measure sedentary lifestyle. Results: Univariate results showed that the majority of respondents had frequent sedentary behavior (93.8%) and a high risk of prediabetes (54.7%) followed by a very high risk of prediabetes (23.4%). Bivariate analysis using the Kendall Tau-C test revealed a significant relationship between a sedentary lifestyle and the incidence of prediabetes with p-value of 0.027 (µ = 0.05). Conclusions: High risk prediabetes was correlate significantly with sedentary lifestyle; therefore, it is suggested to perform physical activity for 30 minutes every day and lower sedentary lifestyle by limiting the use of gadgets and laptops in daily life.